The The effectiveness of digital storytelling on students’ listening skill - Siska, Maria; Armiwati; Habizar (Research and Innovation in Language Learning, 2025)
This study aims to determine the effectiveness of using digital storytelling media in listening skills of grade VIII students in junior high school at Muaro Jambi. This study used a quasi-experimental design with two groups: an experimental group with 26 students who received learning using digital storytelling media, and a control group with 24 students who were taught using conventional methods. Data was collected through pre-tests and post-tests that measured students' listening skills. The results showed a significant improvement in the experimental group. The average pre-test score of the experimental group was 69.61, increasing to 86.76 in the post-test. Meanwhile, the control group only showed an average increase from 65.33 to 67.00. An independent sample t-test showed a statistically significant difference between the two groups (t = 10.75; Sig. = 0.000 < 0.05), meaning the improvement in the experimental group was due to the digital storytelling treatment. The effect size analysis (Cohen's d = 2.92) also showed a large and noticeable impact of using digital storytelling in the learning context. It is concluded that digital storytelling is an effective, interactive, and multimodal learning medium in students' listening skills.